(untitled) (International Journal of Islamic Business, 2024)
In general, Indonesian people still do not understand waqf management in Islam correctly and thoroughly. If Muslims examine the benefits of waqf more deeply, it can be ascertained that the benefits can be reaped in this world and the hereafter. The discourse of productive waqf and cash waqf is echoed in Indonesia by several Indonesian figures, thinkers, and scholars so if the main obstacles to waqf are not addressed, it will have an impact on misuse and fraud in waqf. The Indonesian Waqf Board (BWI) should cooperate with the DSN-MUI to issue this waqf fatwa. This article aims to review and analyze the benefits of waqf insurance and investment benefits in Sharia life insurance based on DSN-MUI Fatwa No. 106 of 2016. This research uses a qualitative method with a literature study approach. The results of this study indicate that the principle of this fatwa uses the legal basis of the Qur’an and Hadith by using the istislahi pattern, which is the consideration of benefits based on general nash. In this pattern, general verses are collected to give birth to several general rules that are used to protect or bring certain benefits. They are based on Maqashid Sharia, so that they can help optimize the waqf program in Indonesia. The issuance of the fatwa on waqf insurance benefits and investment benefits in Sharia life insurance is due to a request from an Islamic financial institution, namely Sun Life Financial Syariah and Al-Azhar Waqf Institution, which applied for the determination of the Sharia aspects of life insurance investment benefits for waqf products and waqf insurance policies. For this reason, this DSN-MUI fatwa can be said to be in accordance with the general principle that fatwas are responsive, proactive and anticipatory.